The Peru of Leguía. Historiographical paths and deviations. - Irurozqui V., Marta (1994)
In this article, the author analyses -with a criticism review of written documents- how the Peruvian historiography has tackled the "elite" behavior during the "Aristocratic Republic" and the "Leguia's Oncenio ". Because of the ideology excess shown in most of the books, is very little what we know about the "elite" performance in this period of time. That's why the author proposes an analysis of the social group mentioned above with a conflict perspective generated in its interior.